2017
DOI: 10.1287/stsy.2017.0002
|View full text |Cite
|
Sign up to set email alerts
|

An Ergodic Control Problem for Many-Server Multiclass Queueing Systems with Cross-Trained Servers

Abstract: Abstract.A Markovian queueing network is considered with d independent customer classes and d server pools in Halfin-Whitt regime. Class i customers has priority for service in pool i for i 1, . . . , d, and may access some other pool if the pool has an idle server and all the servers in pool i are busy. We formulate an ergodic control problem where the running cost is given by a non-negative convex function with polynomial growth. We show that the limiting controlled diffusion is modelled by an action space w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Such queueing systems might be referred to as queueing networks with help. Similar type queueing network is studied in [4] for a M/M/N+M queueing network with ergodic type costs. The service time distributions of the customers at different servers are assumed to be exponential.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Such queueing systems might be referred to as queueing networks with help. Similar type queueing network is studied in [4] for a M/M/N+M queueing network with ergodic type costs. The service time distributions of the customers at different servers are assumed to be exponential.…”
Section: )mentioning
confidence: 99%
“…The main goal of this article is to characterize the value function (2.4) in terms of the solution of HJB (2.5). However, in the many server settings above questions are addressed in [4]. The limiting HJB in [4] has a classical solution which is used to obtain an optimal control for the limiting problem.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…For multiclass multi-pool networks, Ward and Armony [30] have studied blind fair routing policies, and used simulations to validate their performance, and compared them with non-blind policies derived from the limiting diffusion control problem. Biswas [31] recently studied a specific multiclass multi-pool network with "help" where each server pool has a dedicated stream of a customer class, and can help with other customer classes only when it has idle servers. For this network model, the control policies may not be work-conserving, and the associated controlled diffusion has a uniform stability property, which is not satisfied for general multiclass multi-pool networks.…”
Section: Introductionmentioning
confidence: 99%
“…For the same model, Armony and Ward [5] showed that a threshold policy is asymptotically optimal for minimizing the steady-state expected queue length and waiting time subject to a "fairness" constraint on the workload division. Biswas [11] has recently studied a multiclass multi-pool network with "help" under an ergodic cost criterion, where each server pool has a dedicated stream of a customer class, and can help with other customer classes only when it has idle servers. The N-network does not belong to the class of models considered in Biswas [11].…”
Section: Introductionmentioning
confidence: 99%